Ragam Modal Perempuan Perdesaan dalam Menghadapi Perubahan Iklim di Tengah Subordinasi - Widya Hasian Situmeang; Fairuz Rafidah Aflaha (Jurnal Perempuan, 2022)
Climate change causes the emergence of various phenomena in social life. This phenomenon has a tendency to increase uncertainty over the fulfillment of food, clean water needs, health, to the household economy in various communities in rural Indonesia. Women and children are the vulnerable groups who bear more of the burden of climate change. In reality, women are indirectly required to be able to strategize to meet family needs in the midst of the vulnerability of life due to climate change. The strong patriarchal pressure on Indonesian society makes the role of women often invisible and not taken into account in seeking household resilience, especially in rural and coastal areas. This paper aims to identify the characteristics and raise the story of rural and coastal women in Indonesia in the face of climate change. Another thing identified in this study is the variety of strategies used by women, as well as the challenges of subordination they experience. This study was conducted using a literature study method as well as collecting qualitative field findings on the experiences of women facing climate change in various regions in Indonesia. This study draws on the literature from 2010 to 2020 and compares it with field findings on the experiences of women in rural and coastal areas in Java and East Nusa Tenggara in the period 2019 – 2022. The results show that rural and coastal women are proven to continue to carry out various adaptation strategies that tends to be dominated by social capital in facing the challenges of climate change even though its role is not taken into account as a struggle within the community